PENGGUNAAN MEDIA GAMBAR PADA MATA PELAJARAN IPA MATERI RANTAI MAKANAN DI KELAS V SDN 067240 MEDAN TEMBUNG T.P 2024/2025 - Andrian; Bambang Nur Alamsyah; Rahmad Mushlihuddin; Rahayu Nur Syari (STKIP Subang, 2024)
The purpose of this study is to improve student learning outcomes by using picture media in class V SDN 067240 Medan Tembung. This type of research is classroom action research. The image media used in this study is in the form of images of food chains on land and in the sea. In the learning process, image media is used in the initial activity, core activity and final activity. In cycle I, the use of image media in science lessons reached an average class score of 65.7. Then in cycle II, the average score of students increased again to 71.25. This score has reached the KKM and has reached the target where more than 75% of students obtained a score of more than 70.00. The results of the observation of student attitudes, from cycle I to cycle II have increased. This is proven by.